FATA Study: Prevalence of Atrial Fibrillation and Antithrombotic Therapy in Primary Health Care in a Northern City of Portugal - Gomes, Eva (2015)
Introduction: Atrial fibrillation is the most prevalent sustained arrhythmia. The efficacy of oral anticoagulation has been proved in prevention stroke in these patients. However, this seems to be an underutilized treatment.Objectives: to determine the prevalence of known atrial fibrillation in a Primary Health Care population; to identify major comorbidities, current antithrombotic therapy and evaluate their suitability according to the European Society of Cardiology guidelines.Material and Methods: Observational cross-sectional analytical study. Population: all patients aged 30 or above, enrolled in eight Family Health Units of Vila Nova de Gaia and diagnosed with atrial fibrillation.Results: Prevalence of atrial fibrillation was 1.29% (n = 940), being higher in males (p = 0.01) and increasing with age (p < 0.001). The most common comorbidities were hypertension (76.4%), heart failure (32.0%) and diabetes mellitus (28.2%). A total of 52% was performing anticoagulant therapy, 29% antiplatelet agents and 4% both therapies. Of those with low thrombotic risk, 63.6% was wrongly performing some kind of antithrombotic therapy; among patients with high risk or valvular disease 56.8% was properly undergoing anticoagulant therapy.Conclusion: The prevalence of atrial fibrillation as well as the frequency of the main comorbidities associated with it are in line with the majority of studies. Although most patients are undergoing oral anticoagulation, only 56.8% of those with atrial fibrillation was performing adequate antithrombotic therapy as recommended by the European Society of Cardiology guidelines, which denote a marked underutilization of this treatment.Keywords: Atrial Fibrillation; Fibrinolytic Agents; Stroke; Primary Health Care; Portugal.